A nucleação escolar no assentamento Vila Amazônia em Parintins/AM e a precarização das condições de acesso, permanência e qualidade social da educação no campo. - Souza, Rosana Ramos de (2016)
This work arose from my restlessness at the inequalities in educational supply for populations living in the regions furthest from urban nuclei in the Amazon region. In family life and with known people, in social relations built in schools and at work, there is a fragility of knowledge about our own educational reality and, especially, about the schools of the field. In this perspective, the thesis defended here is that the inauguration and functioning of a nucleated school do not guarantee access, student stay and social quality of education; on the contrary: by making rural school transport as the only way to access the school, the government does not guarantee the resources and conditions necessary for satisfactory learning of students who live and study in the field. The work is based on the historical, political, economic and cultural study, in an attempt to understand the multiple determinations that configure education in the field, in the nucleated schools of the Vila Amazônia Settlement. The research seeks to analyze the nucleation process and its reflections on access, permanence and social quality of education offered to students in the Vila Amazônia Settlement in Parintins. In line with this purpose, it was up to us to analyze the interrelationship of the State and social movements at the national level in the guidelines, programs and actions managed for the schools of the field; identify the problems arising from the displacement of students (land and river route) to nucleated schools and their impacts on educational indicators; and analyze educational policies for the field, in the Amazonian context, having as object the nucleated schools of the Vila Amazônia Settlement. The methodological course occurred through bibliographic research, data collection was performed through semi-structured interviews, document analysis, on-site visit, observations, microdata analysis of the School Census, Ideb, income and data on age-grade distortion available on the QEdu platform. Managers, residents and leaders of the respective communities surveyed were interviewed, technicians responsible for the Coordination of Rural Education, the coordinator of Rural School Transport and the former Secretary of Education, who served at the head of the implementation of nucleated schools in the late 1990s. Nucleation was expanded in Brazil as opposed to the weaknesses of the multiserial classes; however, it turns out that it causes two problems: first, it closes schools in communities; and, second, does not guarantee rural school transport with quality, punctuality and safety. Nucleation requires the operation of school transport, without transportation the student's access is unfeasible; recurring paralizations may be found, whether due to lack of fuel, payment of carriers or maintenance of buses and intrafecability of the road, factors that directly compromise the social quality of education. It is pointed out the need to readjust the school calendar in an alternation regime, in order to reduce the negative impacts during the rainy season, a period in which greater difficulties occur in transport. This action is aimed at demonstrating the Community, through the mobilization of social movements with the Municipal Council of Education and SEMED, considering that the road has been without paving for decades, without objective manifestation, concrete manifestation of rulers of the federal, state or municipal levels to improve the living conditions of the population living in the settlement, as well as enable conditions for access, permanence and social quality of education to students.